Si3N4 / Cu connecting piece based on Ag-coated TiH2 composite brazing filler metal and preparation and application of Si3N4 / Cu connecting piece
By using Ag@TiH2 composite solder to generate the TiCu2 enhanced phase and thinned interface reaction layer in Si3N4/Cu connector, the interfacial residual stress problem caused by CTE differences is solved, and the mechanical properties of the connector are significantly improved.
Patent Information
- Application Number
- CN202510050898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
Due to the difference in CTE, the Si3N4/Cu connector produces residual stress at the interface, which reduces the fracture strength and toughness and affects the reliability of the connector.
Ag@TiH2 composite brazing was used for brazing treatment, and the TiCu2 enhanced phase at the submicron scale was generated in situ to improve CTE matching, and thin the interface reaction layer through in situ reaction to optimize the microstructure of the brazing seam.
It significantly improves the mechanical properties of Si3N4/Cu connectors, reduces the thermal stress problems caused by CTE mismatch, and avoids problems such as uneven particle distribution and interface defects.
Smart Images

Figure CN119794486A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a Si3N4 / Cu connector based on Ag@TiH2 composite solder, and preparation and application thereof. Background Art
[0002] Silicon nitride copper clad laminate (Si3N4 / Cu) has become an ideal material for high-power electronic device packaging due to its excellent thermal conductivity, matching coefficient of thermal expansion (CTE) with silicon chips, and good electrical insulation performance. It plays a vital role in high-voltage and high-power application scenarios such as rail transportation, smart grids, and new energy vehicles. However, the CTE of Si3N4 (2.7×10 -6 / ℃) and Cu (19×10 -6 / ℃) has a significant difference in CTE. The different shrinkage degrees of the two during the cooling process will lead to the generation of interface residual stress. This residual stress will significantly reduce the fracture strength and toughness of the Si3N4 near-interface area, causing cracks to initiate or expand under a smaller external load, seriously affecting the reliability of the connector. Effectively alleviating this thermal mismatch is the key to ensuring the reliability of the connector.
[0003] At present, although AgCuTi solder has good wettability and interfacial reaction activity, its high CTE limits its ability to relieve residual stress. In addition, the method of introducing particle reinforcement phase also has problems such as poor particle dispersion, easy agglomeration, and interface porosity induced by reduced solder fluidity and wettability, resulting in poor mechanical properties of silicon nitride copper clad laminate (Si3N4 / Cu) as a connector.
[0004] Therefore, it is necessary to provide a solution to improve the mechanical properties of silicon nitride copper clad laminate (Si3N4 / Cu). Summary of the invention
[0005] In view of this, the present application provides a Si3N4 / Cu connector based on Ag@TiH2 composite solder and its preparation and application, which are used to solve the problem of how to improve the mechanical properties of the Si3N4 / Cu connector.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a Si3N4 / Cu connector, comprising the following steps: S1. The Ag powder and TiH2 powder were ball-milled to obtain a composite powder, and then cold-pressed to obtain an Ag@TiH2 composite solder; S2. The Cu plate and Si3N4 plate which have been respectively polished and cleaned are used as welding pieces, and Ag@TiH2 composite brazing filler metal is used as brazing filler metal to perform brazing treatment, thereby obtaining Si3N4 / Cu connecting parts.
[0007] Preferably, in step S1, the ball milling medium is zirconium oxide with a particle size of 3-10 mm, the initial particle size of Ag powder is 10-20 µm, and the initial particle size of TiH2 powder is 5-10 µm; the ball-to-material ratio of the ball milling is 10:1-2, the ball milling speed is 300-400 rpm, and the ball milling time is 6-8 h.
[0008] Preferably, in step S1, ball milling is performed under inert gas.
[0009] Preferably, in step S1, the mass proportion of Ti in the Ag@TiH2 composite solder is 2-10%.
[0010] Preferably, in step S1, the cold pressing pressure is 400-500 KN and the time is 1-2 min.
[0011] Preferably, in step S2, the polishing step is: using 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper for step-by-step polishing in sequence; the cleaning step is: using anhydrous ethanol for ultrasonic cleaning for 10-15 minutes, and then using acetone for ultrasonic cleaning for 10-15 minutes.
[0012] Preferably, in step S2, the vacuum degree of brazing is 2-3×10 -4 Pa, the brazing pressure is 0.02MPa.
[0013] Preferably, in step S2, the heating process of brazing is: heating to 500-600°C at a heating rate of 10-12°C / min, and keeping warm for 30-40 min, then heating to 750-800°C at a heating rate of 10-12°C / min, continuing to keep warm for 30-40 min, and then heating to 850-900°C at a heating rate of 5-6°C / min, and keeping warm for 5-20 min; after brazing is completed, cool to 400-450°C at a cooling rate of 5-6°C / min and then naturally cool to room temperature.
[0014] In a second aspect, the present application provides a Si3N4 / Cu connector.
[0015] In a third aspect, the present application provides an application of a Si3N4 / Cu connector in the field of electronic devices.
[0016] The beneficial effects of the present application are as follows: Based on the in-situ reaction of the Ag@TiH2 composite solder, the present application in-situ generates a large amount of submicron-scale TiCu2 reinforcement phase in the brazing seam of the Si3N4 / Cu connector, thereby improving the CTE matching between the brazing seam and Si3N4 and improving the mechanical properties of the Si3N4 / Cu connector. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is an electron microscope image of the material obtained in Example 1; Figure 2 This is an electron microscope image of the material obtained in Comparative Example 1; Figure 3 This is a CTE comparison diagram of the brazing seam of the materials obtained in Example 1 and Comparative Example 1; Figure 4 The stress-displacement relationship curves of the materials obtained in Example 1 and Comparative Example 1; Figure 5 The electron microscope comparison diagram of the materials obtained in Example 2 and Example 3 is shown. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The present application provides a method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder, comprising the following steps: S1. The Ag powder and TiH2 powder were ball-milled to obtain a composite powder, and then cold-pressed to obtain an Ag@TiH2 composite solder; S2. The Cu plate and Si3N4 plate which have been respectively polished and cleaned are used as welding pieces, and Ag@TiH2 composite brazing filler metal is used as brazing filler metal to perform brazing treatment, thereby obtaining Si3N4 / Cu connecting parts.
[0020] In the present application, based on the in-situ reaction of the Ag@TiH2 composite solder, a large number of submicron-sized TiCu2 reinforcement phases (Cu-Ti particles) are in-situ generated in the brazing seam of the Si3N4 / Cu connector, and the degree of Si3N4 interface reaction is reduced, resulting in the Si3N4 interface reaction layer being only a single TiN reaction layer, and its thickness is reduced. This change effectively avoids the thermal stress problem caused by the CTE difference in the double reaction layer (TiN+Ti5Si3), and the thinner interface reaction layer helps to reduce the interface brittleness. In addition, compared with the method of adding external reinforcement particles, the present application introduces particle reinforcement phases based on in-situ reaction, which effectively avoids problems such as uneven particle distribution, agglomeration and interface defects, optimizes the microstructure of the brazing seam, significantly reduces the CTE of the brazing seam, improves the CTE matching between the brazing seam and Si3N4, and improves the mechanical properties of the Si3N4 / Cu connector.
[0021] In some embodiments, in step S1, the ball milling medium is zirconium oxide with a particle size of 3-10 mm, the initial particle size of Ag powder is 10-20 µm, and the initial particle size of TiH2 powder is 5-10 µm; the ball-to-material ratio of the ball milling is 10:1-2, the ball milling speed is 300-400 rpm, and the ball milling time is 6-8 h.
[0022] In some embodiments, in step S1, ball milling is performed under inert gas.
[0023] In this embodiment, the inert gas is argon. The function of the inert gas is to prevent the powder from being oxidized.
[0024] In some embodiments, in step S1, the mass proportion of Ti in the Ag@TiH2 composite solder is 2-10%.
[0025] In this embodiment, the type, content and size of the Cu-Ti particles in the brazing seam can be controlled by the TiH2 content. When the Ti content exceeds 2wt.%, a micron-sized TiCu2 reinforcement phase will be generated in the brazing seam, while when the Ti content is lower than 2wt.%, the formation of TiCu2 reinforcement phase (Cu-Ti particles) in the brazing seam is not obvious.
[0026] In some embodiments, in step S1, the cold press forming pressure is 400-500 KN and the time is 1-2 min.
[0027] In this embodiment, the cold press forming tool is a stainless steel mold. Before the cold press forming process, a release agent is applied to the inner wall of the mold to prevent powder from sticking.
[0028] In some embodiments, in step S2, the polishing step is: using 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper for step-by-step polishing; the cleaning step is: using anhydrous ethanol for ultrasonic cleaning for 10-15 minutes, and then using acetone for ultrasonic cleaning for 10-15 minutes.
[0029] In some embodiments, in step S2, the vacuum degree of brazing is 2-3×10 -4 Pa, the brazing pressure is 0.02MPa.
[0030] In some embodiments, in step S2, the heating process of brazing is: heating to 500-600°C at a heating rate of 10-12°C / min, and keeping the temperature for 30-40min, then heating to 750-800°C at a heating rate of 10-12°C / min, and keeping the temperature for 30-40min. Then heating to 850-900°C at a heating rate of 5-6°C / min, and keeping the temperature for 5-20min. After brazing is completed, cooling to 400-450°C at a cooling rate of 5-6°C / min, and then naturally cooling to room temperature.
[0031] The present application provides a Si3N4 / Cu connector.
[0032] The present application provides an application of a Si3N4 / Cu connector in the field of electronic devices.
[0033] The present solution is further described below through specific embodiments.
[0034] Example 1 A method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder comprises the following steps: S1. In an argon atmosphere, 180 g of Ag powder with an initial particle size of 10 µm, 20 g of TiH2 powder with an initial particle size of 5 µm, and 3 mm zirconia balls were placed in a planetary ball mill. The ball-to-material ratio was 10:1. The powder was milled at 300 rpm for 6 h to obtain a composite powder. 0.6 g of the composite powder was placed in a stainless steel mold with a release agent coated on the inner wall. A hydraulic press was used to apply a hydraulic pressure of 400 KN for 1 min to obtain an Ag@TiH2 composite solder. S2. The oxygen-free Cu sample (size: 3mm×3mm×2mm) and Si3N4 sample (size: 10mm×10mm×1mm) were polished step by step with 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper, respectively. After polishing, they were first ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then ultrasonically cleaned with acetone for 10 minutes. After cleaning, the samples were placed in a 60℃ oven for 120 minutes. The dried samples were assembled with Ag@TiH2 composite solder and placed in a vacuum oven with a vacuum degree of 2×10 -4 Pa, a vacuum tube furnace with a pressure of 0.02MPa, heated to 500℃ at a heating rate of 10℃ / min, and kept at this temperature for 30min, then continued to heat to 750℃ at the same rate, kept warm for 30min again, then heated to 850℃ at a heating rate of 5℃ / min, and kept at this temperature for 5min. After brazing, cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature in the furnace to obtain Si3N4 / Cu connecting parts.
[0035] Example 2 A method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder comprises the following steps: S1. In an argon atmosphere, 190 g of Ag powder with an initial particle size of 10 µm, 10 g of TiH2 powder with an initial particle size of 5 µm, and zirconia balls with a particle size of 5 mm were placed in a planetary ball mill, and the ball-to-material ratio was 10:1. The mixture was milled at a speed of 300 rpm for 6 h to obtain a composite powder. 0.6 g of the composite powder was placed in a stainless steel mold with a release agent coated on the inner wall. A hydraulic press was used to apply a hydraulic pressure of 400 KN for 1 min to obtain an Ag@TiH2 composite solder. S2. The oxygen-free Cu sample (size: 3mm×3mm×2mm) and Si3N4 sample (size: 10mm×10mm×1mm) were polished step by step with 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper, respectively. After polishing, they were first ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then ultrasonically cleaned with acetone for 10 minutes. After cleaning, the samples were placed in a 60℃ oven for 120 minutes. The dried samples were assembled with Ag@TiH2 composite solder and placed in a vacuum oven with a vacuum degree of 2×10 -4 Pa and a pressure of 0.02MPa, heated to 500℃ at a heating rate of 10℃ / min, and kept at this temperature for 30min, then continued to heat to 750℃ at the same rate, kept warm for 30min again, then heated to 900℃ at a heating rate of 5℃ / min, and kept at this temperature for 20min. After brazing, cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature in the furnace to obtain Si3N4 / Cu connecting parts.
[0036] Example 3 A method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder comprises the following steps: S1. In an argon atmosphere, 196 g of Ag powder with an initial particle size of 10 µm, 4 g of TiH2 powder with an initial particle size of 5 µm, and zirconia balls with a particle size of 3 mm were placed in a planetary ball mill, and the ball-to-material ratio was 10:1. The powder was milled at a speed of 300 rpm for 6 h to obtain a composite powder. 0.6 g of the composite powder was placed in a stainless steel mold with a release agent coated on the inner wall. A hydraulic press was used to apply a hydraulic pressure of 400 KN for 1 min to obtain an Ag@TiH2 composite solder. S2. The oxygen-free Cu sample (size: 3 mm × 3 mm × 2 mm) and the Si3N4 sample (size: 10 mm × 10 mm × 1 mm) were polished step by step with 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper, respectively. After polishing, they were first ultrasonically cleaned with anhydrous ethanol for 10 min, and then ultrasonically cleaned with acetone for 10 min. After cleaning, the samples were placed in an oven at 60 ° C for 120 minutes. The dried samples were assembled with Ag@TiH2 composite solder and placed in a vacuum oven with a vacuum degree of 2×10-4 Pa and a pressure of 0.02MPa, heated to 500℃ at a heating rate of 10℃ / min, and kept at this temperature for 30min, then continued to heat to 750℃ at the same rate, kept warm for 30min again, then heated to 850℃ at a heating rate of 5℃ / min, and kept at this temperature for 5min. After brazing, cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature in the furnace to obtain Si3N4 / Cu connector.
[0037] Comparative Example 1 A method for preparing a Si3N4 / Cu connector comprises the following steps: The oxygen-free Cu sample (size of 3 mm × 3 mm × 2 mm) and the Si3N4 sample (size of 10 mm × 10 mm × 1 mm) were polished step by step with 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper, respectively. After polishing, they were first ultrasonically cleaned with anhydrous ethanol for 10 min, and then ultrasonically cleaned with acetone for 10 min. After cleaning, the samples were placed in an oven at 60 ° C for 120 minutes. The dried samples were assembled with AgCuTi solder (commercially available Ag-26.7Cu-4.5Ti (wt.%) AgCuTi solder) and placed in a vacuum oven with a vacuum degree of 2×10 -4 Pa, a vacuum tube furnace with a pressure of 0.02MPa, heated to 500℃ at a heating rate of 10℃ / min, and kept at this temperature for 30min, then continued to heat to 750℃ at the same rate, kept warm for 30min again, then heated to 850℃ at a heating rate of 5℃ / min, and kept at this temperature for 5min. After brazing, cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature in the furnace to obtain Si3N4 / Cu connecting parts.
[0038] Test and Evaluation The electron microscope images of the Si3N4 / Cu connectors obtained in Example 1 and Comparative Example 1 are shown in Figure 2. Figure 1 As shown, the results of Comparative Example 1 are as follows Figure 2 shown.
[0039] Figure 1 In the brazing process, the TiCu2 particles in the brazing seam are evenly distributed, and no particle agglomeration is observed. Due to the formation of TiCu2 particle phase in the brazing seam, the degree of Si3N4 interface reaction is reduced, resulting in the Si3N4 interface reaction layer being only a single TiN reaction layer, and its thickness is reduced. This change effectively avoids the thermal stress problem caused by the CTE difference in the double reaction layer, and the thinner interface reaction layer helps to reduce the interface brittleness. Figure 2In the experiment, the brazing seam of the connector was mainly composed of wavy Ag-Cu eutectic structure, and a uniformly distributed particle reinforcement phase could not be formed in the brazing seam. In addition, when AgCuTi brazing filler metal was used, the Si3N4 interface reaction layer was a typical TiN+Ti5Si3 double reaction layer.
[0040] The CTE of the brazing seam in the Si3N4 / Cu connector of Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 3 As shown, the results show that the CTE of the brazing seam in the Si3N4 / Cu connector obtained in Example 1 is significantly reduced, and the CTE matching with Si3N4 is greatly improved. The stress-displacement relationship curves of the Si3N4 / Cu connectors obtained in Example 1 and Comparative Example 1 are tested, and the results are as follows Figure 4 As shown, it is explained that the Si3N4 / Cu connector obtained in the present application has good mechanical properties.
[0041] Comparative test of the electron microscope images of the Si3N4 / Cu connectors obtained in Example 2 and Example 3, the results are as follows Figure 5 As shown, it means that when the TiH2 content is low, the Ti in the solder can be completely dissolved in the liquid phase, so no obvious Cu-Ti particles are formed in the brazing seam; when the TiH2 content is too high, micron-sized CuTi particle reinforcement phase will be generated in the brazing seam.
[0042] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder, characterized in that: The following steps are involved: S1. The Ag powder and TiH2 powder were ball-milled to obtain a composite powder, and then cold-pressed to obtain an Ag@TiH2 composite solder; S2. The Cu plate and Si3N4 plate, which have been polished and cleaned, are used as the welded parts, and the Ag@TiH2 composite brazing material is used as the brazing material to perform brazing treatment to obtain the Si3N4 / Cu connector.
2. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S1, the ball milling medium is zirconium oxide with a particle size of 3-10 mm, the initial particle size of Ag powder is 10-20 µm, and the initial particle size of TiH2 powder is 5-10 µm; the ball-to-material ratio of the ball milling is 10:1-2, the ball milling speed is 300-400 rpm, and the ball milling time is 6-8 h.
3. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S1, the ball milling is performed under an inert gas.
4. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S1, the mass proportion of TiH2 in the Ag@TiH2 composite solder is 2-10%.
5. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S1, the cold pressing pressure is 400-500 KN and the time is 1-2 min.
6. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S2, the polishing step is: using 400 mesh, 600 mesh, 1200 mesh, and 2000 mesh sandpaper for step-by-step polishing; the cleaning step is: using anhydrous ethanol for ultrasonic cleaning for 10-15 minutes, and then using acetone for ultrasonic cleaning for 10-15 minutes.
7. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S2, the vacuum degree of brazing is 2-3×10 -4 Pa, and the brazing pressure is 0.02MPa.
8. The method for preparing a Si3N4 / Cu connector based on Ag@TiH2 composite solder according to claim 1, characterized in that: In step S2, the heating process of brazing is as follows: heating to 500-600°C at a heating rate of 10-12°C / min, and keeping warm for 30-40 min, then heating to 750-800°C at a heating rate of 10-12°C / min, keeping warm for 30-40 min, and then heating to 850-900°C at a heating rate of 5-6°C / min, and keeping warm for 5-20 min; after brazing is completed, cooling to 400-450°C at a cooling rate of 5-6°C / min and then naturally cooling to room temperature.
9. A Si3N4 / Cu connecting piece obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the Si3N4 / Cu connector as claimed in claim 9 in the field of electronic devices.
Citation Information
Patent Citations
Method for preparing abrasion-resistant ceramic lining plate by using active soldering method
CN101696122A
Titanium-containing active brazing filler metal and preparation method and application thereof
CN114029651A
Silver-copper-titanium brazing filler metal and preparation method and application thereof
CN116038179A
Ceramic copper-clad substrate and preparation method thereof
CN118053841A
Si3N4 ceramic Cu-coated plate and preparation method thereof
CN118418537A